If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x=4+3x-1
We simplify the equation to the form, which is simple to understand
3x=4+3x-1
We move all terms containing x to the left and all other terms to the right.
+3x-3x=+4-1
We simplify left and right side of the equation.
0x=+3
0=3
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 10x-(2x+4)=60 | | -(12-2x)=-7 | | .2x+c=6 | | x^2-12x+81=0 | | 0.5(4-3)2=x | | 0.5(4-1)2=x | | 0.5(5-3)2=x | | 0.5(5-3)=x | | 0.5(5-2)2= | | y+2.9=5.65 | | 0.5(5-3)2= | | 0.5(5-3)= | | Ln(7)-ln(x)=-0.06 | | 3(6-4r)=7(-7-r) | | u-9.45=3.29 | | 2x(lnx)+2=0 | | x-4.71=6.9 | | x-4.71=69 | | w+2.2=8.87 | | u-12.8=8 | | x=9+-5 | | 8x+7y+9z=1 | | -2.7+a=-6.4 | | 15m^2-6m=0 | | 5i(2i-7)=0 | | 43+78= | | 5cos(x+1)=1 | | 2(4x+3)(3x+5)= | | 2(4x+3)(3x+5)=X^2+58x+B | | 38a+14=15 | | 8s^2-80s+30=-10 | | 4(h+5)60= |